Foliar anatomy of clausena anisata (willd.) hook: a south African medicinal plant - Lawal, I.O.; Uzokwe, Veronica N.E.; Rafiu, B.; Afolayan, A.J. (African Journals Online, 2018)
Clausena anisata (Willd) Hook, the only species in the African continent, out of the 15 species of the genus distributed worldwide. It is regarded as a threatened species in the Southern region of Africa. It distribution spread across Africa to South-East Asia. C. anisata has a wide range of ethnopharmacological importance such as ear sickness, stomach-ache, infections associated with tuberculosis, oral candidiasis, fungal infections of the skin as well as measles and bronchial problem. The efficacies of the leaves of C. anisata have been validated by several authors to have antimicrobial properties especially Mycobacterium tuberculosis and Mycobacterium bovis. The leaves had been ranked high among its morphological parts as being used for the treatment of tuberculosis among the indigenous people of Africa. Despite the numerous studies on the pharmacological profile of the plant, there still exists a dearth of scientific literature on the foliar micromorphology of this medicinal plant. The foliar anatomy of the leaves of C. anisata was examined under Light Microscopy (LM), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDXS) following standard procedures. LM revealed the types of stomata of the leaves (amphistomatic). SEM revealed the presence of the whip like trichomes with its uniqueness to the plants. EDXS revealed the chemical composition of the foliar appendages which indicates the presence Ca, Mg, S, and Fe. The indication of the mineral elements could be helpful in the regulation of herbal drug compositions and reduction of their toxicities.